Buffer-Aided diamond relay network with block fading - Simoni, Renato; Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert; Pierucci, Laura; Fantacci, Romano (2015 IEEE International Conference on Communications (ICC), 2015)
A simple diamond half-duplex relay network composed of a source, two half-duplex relays, and a destination is considered, where no direct link between the source and the destination is exists. For this network, we investigate the achievable rate when the relays are equipped with buffers. Buffer-aided relays can receive data from the source, store it in their buffers, and forward it to the destination when the channel conditions are more advantageous. Thereby, buffering enables adaptive scheduling of the transmissions and receptions over time, which allows the network to better exploit the diversity offered by the fading channel. For the considered network, because of the half-duplex relays, four transmission modes are employed based on whether the relay nodes receive or transmit. Considering these four transmission modes, in this paper, we derive the optimal transmission mode selection policy such that the received data rate at the destination is maximized. Furthermore, based on numerical examples, we show that the proposed protocol outperforms the existing protocols for the considered network in the literature.<br
Keywords: Protocols; Delays; Fading; Diamonds; Relay networks (telecommunications); Signal to noise ratio